Machine Learning Indices, Political Institutions, and Economic Development - Klaus Gründler; Tommy Krieger (Center for Economic Studies and ifo Institute (CESifo), 2018)
We present a new aggregation method - called SVM algorithm - and use this technique to produce novel measures of democracy (186 countries, 1960-2014). The method takes its name from a machine learning technique for pattern recognition and has three notable features: it makes functional assumptions unnecessary, it accounts for measurement uncertainty, and it creates continuous and dichotomous indices. We use the SVM indices to investigate the effect of democratic institutions on economic development, and find that democracies grow faster than autocracies. Furthermore, we illustrate how the estimation results are affected by conceptual and methodological changes in the measure of democracy. In particular, we show that instrumental variables cannot compensate for measurement errors produced by conventional aggregation methods, and explain why this failure leads to an overestimation of regression coefficients.
Keywords: C26; C43; N40; O10; P16; P48; 330; democracy; development; economic growth; estimation bias; indices; institutions; machine learning; support vector machines